Project Management for Scientific Research: Strategy, Leadership, and Implementation - Dutta, Arpan (United States, 2025)
Scientific research in academia and industry nowadays is frequently carried out via research, development, and innovation projects where project management is usually employed to ensure optimal performance and outcome. However, traditional project management often fails to address the volatility and uncertainty intrinsic to scientific research, and developing an adaptive project management framework is essential to secure project success. This work presents the development of such a framework consisting of models for strategy, leadership, and implementation designed for scientific research projects in academia and customized for a small (20 workers) academic research group. The framework and the models therein are constructed through literature review and developed via qualitative action research, while their relevance is evaluated through quantitative survey research. The developed project management framework suggests a blue-ocean model for project strategy, a lean-hybrid (combination of waterfall, agile, and lean principles) model for project implementation, and a transformational (middle-of-the-road) model for project leadership. The reported findings offer a project management framework having models that are applicable for scientific research not only in academia but also in small innovation-based startups. In addition, the development method provides a hands-on approach to the practitioners of scientific research in academia and industry to enable project management as a change.
2025 7th International Congress on Human-Computer Interaction, Optimization and Robotic Applications (ICHORA)